Pengembangan Media “Smart MAV” Berbasis Direct Instruction dalam Pembelajaran Keterampilan Berbicara Bahasa Indonesia - Yukhsan Wakhyudi; Yusup Wibisono (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2022)
This research is conducted to produce and develop audio and visual learning media to improve students understanding of speaking skills. The media is in the form of Smart MAV based on direct instruction. The subject of this research is the students of Indonesian Language Education at Peradaban University. This research belongs to research and development (R&D). This research uses the 4D model. They are: 1) define, 2) design, 3) development, and 4) dissemination. However, the result of this study is only at the development stage, which is product design and validation. Furthermore, data collection activities in this study were carried out through interviews, questionnaires, and observation. The data analysis used descriptive statistics. Based on the research, the result shows Smart MAV based on direct instruction is feasible and valid to use by the validators with a percentage of 93% (excellent), and the results of the material expert validation test with a rate of 83.21% (excellent). These results indicate that the developed media (Smart MAV) is feasible.